1998
DOI: 10.2307/3284522
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Host Age and Size to the Aggregated Distribution of Parasites in Yellow Perch, Perca flavescens, from Garner Lake, Alberta, Canada

Abstract: The independent effects of host age and size on parasite abundance are examined in yellow perch from Garner Lake in east-central Alberta. Older, larger perch tend to have more species of parasites combined with larger parasite infrapopulations. Sexual size dimorphism in perch generates 2 different size classes within each age class >2+ yr, thus allowing the opportunity to separate the effects of age and size on the recruitment of parasites by perch. The abundances of Diplostomum adamsi and Bothriocephalus sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 9 publications
2
45
1
1
Order By: Relevance
“…Also studying the parasitic fauna of fish from lakes, Molloy et al (1995) reported low infection by cestodes in trout, in contrast to our results. Contrary to the present results, Zelmer & Arai (1998) reported a significant increase in the plerocercoid abundance in female perch.…”
Section: Discussioncontrasting
confidence: 99%
“…Also studying the parasitic fauna of fish from lakes, Molloy et al (1995) reported low infection by cestodes in trout, in contrast to our results. Contrary to the present results, Zelmer & Arai (1998) reported a significant increase in the plerocercoid abundance in female perch.…”
Section: Discussioncontrasting
confidence: 99%
“…This among host species difference may be attributable to physical and ecological characteristics of the hosts. Larger individuals, in this case R. quelen, may accumulate larger infrapopulations due to greater age or by feeding higher in the food web (Zelmer & Arai, 1998;Bell & Burt, 1991). Of interest here are general trends across host species, such as the potential influences of host sex and body size on infrapopulations and the relationship between infrapopulation size and host condition.…”
Section: Discussionmentioning
confidence: 99%
“…Fish standard length is a correlate of age (Shotter, 1976), and is one of the most important factors influencing parasite population sizes (Dogiel, 1961). According to Zelmer & Arai (1998), increases in parasite infrapopulation sizes are expected to increase with host age (and host length) as a result of simple accumulation. This scenario requires parasites with direct life-cycles or which use intermediate hosts whose consumption is not limited to one phase of host development.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is a positive relationship between the level of parasitic infection and the size and age of the host fish (Dogiel, 1970;McKeown and Irwin, 1997;Zelmer and Arai, 1998;Aydogdu et al, 2003). In the present study, the infection prevalence and mean intensity values changed as the size and age of the fish varied.…”
Section: Discussionmentioning
confidence: 99%